Finite Element Analysis and Fabrication of Voronoi Perforated Wrist Hand Orthosis Based on Reverse Engineering Modelling Method - Zakki Fuadi Emzain; Nanang Qosim; AM. Mufarrih; Syamsul Hadi (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Other than surgery, post-stroke spasticity, fractures due to accidents, sports injuries, and musculoskeletal disorders due to office work on the wrist can be treated using a wrist-hand orthosis. The customized conventional methods usually have some drawbacks, which are more expensive, take a long time to manufacture, and require expert skills from medical therapists. The presence of reverse engineering (RE) technology can be applied in the medical field, such as the manufacture of prosthetic or orthosis devices. This study aims to develop a reverse engineering-based wrist-hand orthosis design, analyze it using the finite element method, and fabricate it. Research methods included 3D scanning, CAD modelling, model analysis, 3D printing, and postprocessing. The model material used was PLA with variations in the thickness of 5 mm, 5.5 mm, and 6 mm, and the load values range from 0 N to 30 N. The results of the equivalent stress analysis showed that the 5 mm thickness model could withstand a load of 30 N with a maximum equivalent stress of 23.46 MPa. With a safety factor value of 2.56, it was still relatively safe, and a critical area was at the back end of the model's palm between the thumb and index finger. The equivalent elastic strain and deformation results also had the same graphic trend with the maximum values for the same model, which were 0.0076 mm and 0.614 mm, respectively. The 3D printing FDM result showed that the Voronoi perforated wrist-hand orthosis prototype was sturdy, fit, and comfortable. It is expected to hold muscle tone and immobilize for hand rehabilitation.